2018
DOI: 10.7717/peerj.4917
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index and pain, disease activity, depression and anxiety in women with fibromyalgia

Abstract: BackgroundObesity is a possible factor which affects severity of symptoms and disease activity in fibromyalgia syndrome (FMS). The aim of our study was to determine the association between body mass index (BMI) and pain, tender point count (TPC), disease activity, anxiety and depression in patients with FMS.MethodsThis was a descriptive study. A total of 124 female FMS patients between 18 and 55 years of age were enrolled. FMS patients were evaluated with visual analog scale (VAS), fibromyalgia impact question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 40 publications
(59 reference statements)
2
28
1
1
Order By: Relevance
“…All these studies were performed with individuals who were obese, or suffered from severe obesity. It is important to acknowledge that weight gain is associated with an increase in the prevalence of musculoskeletal pain in different body sites [ 30 , 31 ], and that being overweight or obese increase the risk of developing musculoskeletal disorders [ 32 ]. In addition, individuals with severe obesity are also more likely to report pain in various places [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies were performed with individuals who were obese, or suffered from severe obesity. It is important to acknowledge that weight gain is associated with an increase in the prevalence of musculoskeletal pain in different body sites [ 30 , 31 ], and that being overweight or obese increase the risk of developing musculoskeletal disorders [ 32 ]. In addition, individuals with severe obesity are also more likely to report pain in various places [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…High body weight and ankle/foot weight overload may increase the risk of and worsen joint pain [50]. Other studies comparing different categories of BMI found an association between increased BMI levels and increased pain prevalence [30,31]. The lower percentage of total fat was also associated with ankle/foot pain.…”
Section: Mendonça Et Almentioning
confidence: 99%
“…We tested Model 1, in which average daily physical activity was the predictor as used on past reports, 20 , 37 pain intensity (BPI) was the dependent variable, and average daily state pain catastrophizing was the moderator of the relationship between average physical activity and average pain intensity controlling (covariates) for FM symptoms (FIQR) and BMI following prior literature. 25 , 50 …”
Section: Methodsmentioning
confidence: 99%
“…FIQ is the most commonly used test to measure the severity of disease in FM patients, but whether it is indicative of inflammation is not clear. In some studies, it was found to be associated with indicators of inflammation in FM, while in some studies, it was not correlated with the markers of inflammation [9,29,30]. When Gunturk et al [29] evaluated the parameters of arterial stiffness in FM patients, they found that the parameters of arterial stiffness were highly correlated with the FIQ score.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 levels affect the severity of FM [4,6,9]. There are also studies showing that FM is associated with inflammation markers, systemic inflammation, and neuroinflammation [10,11].…”
mentioning
confidence: 99%